The Transformation of Arabic Language Learning through Augmented Reality in the Islamic Religious Education Study Programs - Risris Hari Nugraha; Ganjar Eka Subakti; Muhamad Rizka Saomi; Ahmad Nahid Mashury (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
Arabic language learning in Islamic Religious Education (PAI) study program faces several challenges, particularly low student engagement, the persistence of conventional teaching methods, and limited adoption of educational technologies. This study aims to analyze the transformation of Arabic language learning through the integration of Augmented Reality (AR) in Islamic Religious Education programs at public universities. The study was motivated by the dominance of conventional methods, which have proven ineffective in enhancing student motivation, engagement, and learning outcomes, as well as a research gap regarding the use of AR in the context of Arabic language learning grounded in Islamic values. The research employs a qualitative approach using a case study and phenomenological design, involving 45 students and faculty members as key informants through stratified purposive sampling. Data were collected via interviews, observations, and documentation, and analyzed thematically while ensuring validity through triangulation and member checking. The results indicate that AR significantly enhances students’ understanding and engagement, with average grades increasing from 68.4 to 82.7 and active participation rising from 52% to 84%. AR outperforms conventional digital media due to its interactive, immersive, and contextual nature, particularly in Islamic studies content.